2022
DOI: 10.3390/earth3010027
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic in Groundwater Sources from Selected Communities Surrounding Taal Volcano, Philippines: An Exploratory Study

Abstract: Arsenic (As) is a highly toxic, carcinogenic trace metal that can potentially contaminate groundwater sources in volcanic regions. This study provides the first comparative documentation of As concentrations in groundwater in a volcano-sedimentary region in the Philippines. Matched, repeated As measurements and physico-chemical analyses were performed in 26 individual wells from 11 municipalities and city in Batangas province from July 2020 to November 2021. Using the electrothermal atomic absorption spectrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…Dangerous arsenic concentration was detected from the wells and other water sources from the surrounding municipalities of Taal volcano. The groundwater is reported to have the volcanic rocks and its contents (Apostol et al, 2022). In relation to this study, Taal Lake has no direct contact to the volcanic materials unlike the groundwater.…”
Section: Heavy Metal Concentration In Taal Lake Watermentioning
confidence: 64%
See 1 more Smart Citation
“…Dangerous arsenic concentration was detected from the wells and other water sources from the surrounding municipalities of Taal volcano. The groundwater is reported to have the volcanic rocks and its contents (Apostol et al, 2022). In relation to this study, Taal Lake has no direct contact to the volcanic materials unlike the groundwater.…”
Section: Heavy Metal Concentration In Taal Lake Watermentioning
confidence: 64%
“…Another factor that may also explain the presence of arsenic in the soil is the ground water contamination. Higher arsenic concentration was detected from the wells and other water sources from the different municipalities surrounding Taal volcano in year 2020 than 2021 (Apostol et al, 2022). Their study explained that the movement of the groundwater had an access to the volcanic contents and also in the soil .…”
Section: Heavy Metal Concentration In the Soilmentioning
confidence: 94%
“…Arsenic levels from 26 locations in Batangas near the volcano from 2020 to 2021 were found to be significantly and consistently higher than the World Health Organization (WHO) and Philippine National Standards for Drinking Water (PNSDW) 10 ppb limit. The 2020 levels were comparatively higher than those of 2019, which is believed to be caused by a more active Taal volcano [38]. These findings, in conjunction with various other factors, served as primary motivations for the initiation of the study.…”
Section: Total Suspended Sediment and Arsenic In Pasig Rivermentioning
confidence: 88%
“…A closer look at Table 2 revealed that a higher concentration of Ar, (0.27 mg/L) from snail muscles was detected in site A, which was higher than the national acceptable limit in drinking water set at 0.010 mg/L, although the safe limit for mollusk as food is set at 1mg/kg. Nevertheless, this detection may call for some concerns due to the continued consumption of the snails by the locals because this trace metal, aside from being highly toxic and carcinogenic (Apostol et al 2022), can biomagnify along with other toxic pollutants, that is, to increase in concentration in the living organisms successively at higher levels in the food chain (Hepp 2017).…”
Section: Micronucleation By Sampling Sitesmentioning
confidence: 99%